P-Benzoquinone anodic degradation by carbon black diamond composite electrodes - Ajeel, M.A.; Aroua, M.K.; Daud, Wan Mohd Ashri Wan (Elsevier, 2015)
In this work, p-benzoquinone (p-BQ) electro-degradation in three carbon black diamond (CBD) composite electrodes is studied under conditions of 200 mg/L initial concentration, 45 mA/cm(2) applied current density, pH 3, and 0.25 M Na2SO4 as a supporting electrolyte. The performance of the CBD electrodes was compared with that of a platinum electrode. Results showed that the optimal p-BQ degradation, COD removal efficiency, and current efficiency may be obtained from the CBD electrode containing 20 carbon black (20CBD). After 20 min of electro-degradation, p-BQ removal on 20CBD reached 96 at pH 6 and 61.5 at pH 3. However, after 180 min of p-BQ degradation, COD removal on this electrode reached 45 at pH 6 and 70 at pH 3. Increases in applied current during p-BQ electro-oxidation were related to the initial p-BQ concentration. Significant differences were observed in the solution containing 200 mg/L p-BQ as the current density was increased from 20 mA/cm(2) to 45 mA/cm(2); no such effects were observed in the solution with 1000 mg/L p-BQ. (C) 2015 Elsevier Ltd. All rights reserved.